Mendeleev Table: a Proof of Madelung Rule and Atomic Tietz Potential - Belokolos, E.D. (Symmetry, Integrability and Geometry: Methods and Applications, 2017)
We prove that a neutral atom in mean-field approximation has O(4) symmetry and this fact explains the empirical [n+l,n]-rule or Madelung rule which describes effectively periods, structure and other properties of the Mendeleev table of chemical elements.